Antimicrobial Susceptibility Trends in E. coli Causing Pediatric Urinary Tract Infections in the United States - Simren Mahajan; Neena Kanwar; Gina M. Morgan; Rodrigo E. Mendes; Brian R. Lee; Dithi Banerjee; Rangaraj Selvarangan (Pathogens)
Urinary tract infections (UTIs) are among the most common pediatric infections. This study evaluated the antimicrobial susceptibility patterns of 3511 uropathogenic E. coli (UPEC) isolated from pediatric patients in the United States from 2014 to 2023. The database from the SENTRY antimicrobial surveillance program from 89 medical centers was utilized as a data source. The antimicrobial susceptibility was tested using the microbroth dilution technique against 24 antimicrobial agents. MICs were determined using the CLSI/EUCAST/FDA breakpoint criteria. All the antimicrobials reported susceptibility rates above 80% except for tetracycline (76.2%), trimethoprim–sulfamethoxazole (69.7%), and ampicillin–sulbactam (55.7%). During the study period, the susceptibility rates remained stable for most antimicrobial agents. However, significant differences were observed among age, gender, and U.S. census regions, with the Middle Atlantic showing the lowest and the Mountain region the highest susceptibility rates, for most antimicrobials. The incidence of ESBL UPEC increased from 7.1% to 10.8% between 2014 and 2023, while the prevalence of the MDR phenotype remained relatively stable. The prevalence of both ESBL and MDR phenotypes was highest among infants and young children (0–24 months), with the highest resistance rates from the Pacific region. Knowledge of the landscape of antibiotic resistance in pediatric UPEC will help healthcare providers to better tailor empiric treatment regimens for most UTI infections.